2003
DOI: 10.1046/j.1466-7657.2003.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent mothers’ utilization of contraceptive services in South Africa

Abstract: Young mothers require more knowledge to enable them to make better informed decisions, and the services need to become more readily accessible and user friendly to adolescents. Reproductive health services provided specifically to adolescents could enhance the utilization of such services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…Overall, they reported that ECPs were not appropriate for women younger than 18 and admitted to denying young people access to EC. The studies from the Limpopo Province corroborate this finding and add that providers often impose age restrictions that prevent young women from accessing contraception methods 13,24 . The extent of this occurrence, however, is unknown; indeed, according to McFadyen et al 7 almost two thirds of providers felt that there was no minimum age for them to prescribe EC.…”
Section: Provider Attitudes To Ecmentioning
confidence: 58%
See 3 more Smart Citations
“…Overall, they reported that ECPs were not appropriate for women younger than 18 and admitted to denying young people access to EC. The studies from the Limpopo Province corroborate this finding and add that providers often impose age restrictions that prevent young women from accessing contraception methods 13,24 . The extent of this occurrence, however, is unknown; indeed, according to McFadyen et al 7 almost two thirds of providers felt that there was no minimum age for them to prescribe EC.…”
Section: Provider Attitudes To Ecmentioning
confidence: 58%
“…Indeed, most studies suggest that very few people have even heard of it [13][14][15] . A study of adolescent mothers in one South African province, for example, found that approximately one fifth knew about the existence of EC and that even fewer knew that ECPs could be taken to prevent pregnancy after unprotected intercourse 13 .…”
Section: Awareness Of Emergency Contraceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence suggests that it is not simply lack of knowledge that results in underutilisation of EC but also the attitudes of health providers and their reluctance to provide it 6 7. A study of adolescent mothers in South Africa found that the attitudes of providers play a critical role in facilitating access to EC 12. Provider knowledge and acceptance of EC constitute a crucial link to improving access to women who need it 12 13.…”
Section: Introductionmentioning
confidence: 99%